Control Your Emotions or Follow Your Heart: Discussing the Contradictions In Psychology of Emotions and Behaviour: Exploring the Dichotomy in the Psychology of Emotions (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Get a grip… controlyour emotions… don’t let your feelings get in the way! Listen to your heart…getin touch with your emotions… express yourself! These messages from the academiccommunity, as well as popular treatments of emotion, are contradictory. Therationalist history of Western thought portrays emotions as fundamentallyflawed, and something we must therefore control (Haidt, 2001). Yet, there hasbeen another voice in history—and one echoed in recent evolutionary treatmentsof emotion—that suggests that emotions are wise and not to be ignored (Buss,2001; Clore, in press; Keltner & Haidt, 1999; Ketelaar, 2004, 2005;Ketelaar & Clore, 1997).